ILMU MENDIDIK TEORETIS: BIJAK DALAM BERMEDIA SOSIAL - Bustomi Arifin (Universitas Narotama, 2018)
Social media today is a medium that many access by almost all levels of society in Indonesia. This is because almost all levels of society can easily access social media. Ease in social media makes all the people of Indonesia easy to receive information from all over Indonesia and the world. Ease in accessing social media and the opening of information gates through social media encourages the birth of irresponsible elements by disseminating information that is inconsistent with the reality. The issue is growing rapidly among the people of Indonesia, it is given the lack of selective and critical attitude of the people of Indonesia in receiving information contained in social media. Negative impacts that may arise may arise related to selective and critical attitude in receiving information on social media is the diminution of national resilience values. The above issues become the basis of reference for authors in compiling this article. It uses the descriptive method of analysis by using an understanding that Prof. Driyakarna is theoretical educational science. It is expected to encourage Indonesian people to be more selective and critical of information spread across various social media. Key Terms: Social Media, Indonesian Society, Selective, Theoretical Educational Science